The Role of Immunohistochemistry for AMACR/p504s and p63 in Distinguishing Prostate Cancer from Benign Prostate Tissue Samples in Botswana - Ramatlho P; Rugemalila MM; Tawe L; Pain D; Choga OT; Ndlovu AK; Koobotse MO; Lal P; Rebbeck TR; Paganotti GM; Narasimhamurthy M; Kyokunda LT (Research and Reports in Urology)
Pleasure Ramatlho,1,2 Moses Muganyizi Rugemalila,3 Leabaneng Tawe,1,2 Debanjan Pain,4,5 Ontlametse T Choga,1,6 Andrew Khulekani Ndlovu,1 Moses O Koobotse,1 Priti Lal,5 Timothy R Rebbeck,7,8 Giacomo M Paganotti,2,9 Mohan Narasimhamurthy,5 Lynnette Tumwine Kyokunda3 1School of Allied Health Professions, Faculty of Health Sciences, University of Botswana, Gaborone, Botswana; 2Botswana-University of Pennsylvania Partnership, Gaborone, Botswana; 3Department of Pathology, Faculty of Medicine, University of Botswana, Gaborone, Botswana; 4Department of Medicine (Hematology-Oncology), University of Pennsylvania, Philadelphia, PA, USA; 5Hospital of University of Pennsylvania, Philadelphia, PA, USA; 6Botswana Harvard AIDS Institute Partnership, Gaborone, Botswana; 7Division of Population Science, Dana-Farber Cancer Institute, Boston, MA, USA; 8Department of Epidemiology, Harvard T.H. Chan School of Public Health, Boston, MA, USA; 9Division of Infectious Diseases, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USACorrespondence: Pleasure Ramatlho, Pleasure Ramatlho School of Allied Health Professions, Faculty of Health Sciences, University of Botswana, Gaborone, Botswana, Tel +26777572242, Email pleasureram@gmail.comIntroduction: Prostate cancer (CaP) is the most common malignancy and the second leading cause of cancer-related deaths among men in Botswana. Currently, diagnosing CaP relies on examining prostate biopsy samples, which can be challenging due to benign mimics. This study aims to evaluate the potential of Alpha-methyl acyl-CoA racemase (AMACR/p504s) and p63, as diagnostic markers for CaP. This may potentially validate the use of immunohistochemistry for detecting CaP in Botswana, where it is not routinely utilized.Methods: The study included 69 samples, comprising 5 prostatic chip specimens, 50 core biopsies, and 14 radical prostatectomy specimens. These cases were reviewed and categorized into CaP (49 cases) and benign prostatic hyperplasia (BPH) (20 cases). Immunohistochemistry was performed using AMACR/p504s and p63 immunohistochemical stains.Results: The study found that AMACR/p504s had a sensitivity of 96% and a specificity of 95%, while p63 had a sensitivity and specificity of 100%. PSA levels showed significant positive correlation with AMACR/p504s expression (P < 0.00001).Discussion: In this study, we have demonstrated the diagnostic utility of AMACR/p504s and p63 due to their high sensitivity and specificity in detecting CaP in Botswana, where these biomarkers are not yet widely used. Furthermore, utilizing these markers in conjunction with other diagnostic tools, such as PSA levels and morphological evaluation, could improve the diagnostic accuracy, especially in challenging cases where histopathological examination alone may be inconclusive.Keywords: prostate cancer, AMACR/p504s, p63, benign prostatic hyperplasia, Botswana